Analysis of Village Head Election in tha Perspective of Village Autonomy (Study in Tempang 1 Village, Langowan District, Minahasa Regency) - Sisca B. Kairupan,; Margareth I. R. Rantung,; Anggelina V. Tulangow,; Anastasia Mandagi, (Technium Social Sciences Journal, 2023)
This study aims to find out, analyze and describe the election of village heads in Tempang I village, North Langowan sub-district, Minahsa district. The research method used is descriptive qualitative. The results of the study show that the election for the head of the village of Tempang is not optimal, based on 1). Preparations for the election of the committee in the village of Tempang are still said to be lengthy because the committee for the formation of the Village Head Selection Committee is carried out by the head of the BPD who first holds a deliberation meeting for the formation of the committee. 2). Nomination requirements that meet the requirements for candidates to be nominated as village heads in accordance with applicable regulations. 3). Voting The Election Committee compiles, signs and reads the Minutes of Election and submits it to the Chairperson of the BPD for approval from the BPD. 4) Determination. In the Village Pilkades temp 1 only the elected Village Head Candidates sign the Minutes of voting and counting.